Clinicopathological characteristics of invasive stratified mucinous carcinoma of the cervix and the expression and clinical significance of SLC7A11, SLC3A2 and PD-L1 - Lu, Changyu; Zhu, Wei; Han, Xiahui; Du, Xiuzhen; Zhang, Hui; Yao, Qin; Liu, Ting; Zhang, Ce (Frontiers in Oncology, 2024)
IntroductionInvasive Stratified Mucin-producing Carcinoma (ISMC) of the cervix is a newly named cervical adenocarcinoma associated with Human Papilloma virus (HPV). Due to its relative rarity, clinical data, pathological features, and molecular characteristics of ISMC are still under exploration. This study aims to retrospectively analyze the clinical data and pathological features of ISMC patients, summarizing the clinical and pathological morphological characteristics of ISMC. Immunohistochemistry for SLC7A11, SLC3A2, and PD-L1 will be performed on tumor tissues from ISMC patients to preliminarily explore potential therapeutic targets for ISMC.MethodsWe retrospectively reviewed the electronic medical records and pathological slides of 22 ISMC patients, and performed immunohistochemical staining for solute carrier family 7 member 11 (SLC7A11), solute carrier family 3 member 2 (SLC3A2), and programmed death-ligand 1 (PD-L1).ResultsThe patients were aged between 31 and 70 years old. The most common symptoms were abnormal vaginal bleeding and unusual vaginal discharge. HPV testing indicated that the infection rate of HPV type 18 was the highest. All patients underwent extensive hysterectomy and pelvic lymph node dissection. The progression-free survival (PFS) ranged from 3 to 112 months, with a postoperative recurrence rate of 22.7% (5/22). ISMC exhibited diverse characteristic microstructures. Immunohistochemistry results showed that the positive rates of SLC7A11 and SLC3A2 were both 91.0% (20/22). The staining intensity of SLC7A11 in frequent ISMC recurrence cases was significantly stronger than in non-recurrent ISMC cases. PD-L1 positivity was observed in 86.4% (19/22) of cases, defined as having a Combined Positive Score(CPS)≥1.DiscussionISMC demonstrates a high rate of lymph node metastasis and a high recurrence rate, indicating strong invasiveness. Additionally, ISMC exhibits a wide morphological spectrum. SLC7A11, SLC3A2, and PD-L1 are all highly expressed in ISMC tissues. The high expression of SLC7A11 may indicate a high recurrence rate for ISMC. Immunotherapy with checkpoint inhibitors and iron death-related treatments show potential in the treatment of ISMC, with SLC7A11, SLC3A2, and PD-L1 serving as potential therapeutic targets for ISMC.